2013
DOI: 10.1016/s0187-6236(13)71062-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data on SOA formation from mixtures of anthropogenic and biogenic organic compounds

Abstract: RESUMENLos aerosoles orgánicos secundarios (AOS) constituyen una fracción de las partículas atmosféricas. Este tipo de partículas se forman como consecuencia de la reacción de oxidación de ciertos gases orgánicos, lo que conduce a la formación de compuestos de baja volatilidad. Del mismo modo que para otros contaminantes atmosféricos, los modelos de calidad del aire permiten la simulación de partículas, una herramienta muy útil en tareas de gestión de la calidad del aire. Sin embargo, el uso adecuado de estos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous studies have showed that when isoprene is mixed with another aVOC, the SOA particle yields can be reduced (Jaoui et al, 2008;Vivanco et al, 2013;Ahlberg et al, 2017). This may imply that either the potential molecular interactions resulted in higher-volatility products that remained in larger fractions in the gas phase, or that isoprene was scavenging the available OH, thus reducing the SOA particle mass formed from the oxidation of o-cresol.…”
Section: Influence Of Isoprene In Binary Mixturesmentioning
confidence: 99%
“…Previous studies have showed that when isoprene is mixed with another aVOC, the SOA particle yields can be reduced (Jaoui et al, 2008;Vivanco et al, 2013;Ahlberg et al, 2017). This may imply that either the potential molecular interactions resulted in higher-volatility products that remained in larger fractions in the gas phase, or that isoprene was scavenging the available OH, thus reducing the SOA particle mass formed from the oxidation of o-cresol.…”
Section: Influence Of Isoprene In Binary Mixturesmentioning
confidence: 99%
“…Only four representative experiments are shown here in the interest of conciseness. The EUPHORE chamber and the associated analytical techniques are described by Vivanco et al (2011Vivanco et al ( , 2013. The selection of the EUPHORE experiments was based on a consistent estimation of particle concentrations from two different analytical instruments: a tapered element oscillating monitor (TEOM) and a scanning mobility particle siser (SMPS).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we present an intercomparison of different SOA mechanisms, with one-step, two-step and multi-step oxidation reactions for anthropogenic SOA precursors. A comparison of model results against two sets of experiments, performed in two outdoor chambers, UF (University of Florida, USA) and EUPHORE (Ceam, Valencia, Spain;Vivanco et al, 2013) Experiments in UF were performed for individual VOCs (toluene and 1, 3, 5-trimethylbenzene), whereas experiments in EUPHORE were performed with a mixture of four anthropogenic VOCs: toluene (TOL), 1, 3, 5-trimethylbenzene (TMB), o-xylene (OXYL) and octane (OCT).…”
Section: Introductionmentioning
confidence: 99%
“…The ambient atmosphere is a complex mixture of different organic gases, which can interact and mix to form SOA through the same emission source or in the atmospheric transport (Voliotis et al, 2022;Malik et al, 2018;Luo et al, 2015).The oxidation of organic gases with other VOCs produces more SOA with monoterpenes or sesquiterpenes in the mixed systems (Vivanco et al, 2011;Vivanco et al, 2013;Emanuelsson et al, 2013). Most of the monoterpenes and sesquiterpenes contain endocyclic carbon-carbon double bonds.…”
mentioning
confidence: 99%